Study MetheletetraHydrofolatredctase (MTHFR) Gene Polymorphism in Myocardial Infarction Patients in Babylon Province/ Iraq - Mona Al-Terehi (Journal of Global Pharma Technology, 2017)
The present study was aimed to investigate MetheletetraHydrofolatredctase (MTHFR) gene which related to acute myocardial infarction (MY) patients using restriction fragment length polymorphism (RFLP-PCR) technique, the results show that the homozygote TT genotype was (23.3%) in patients and (30.0%) in control with non-significant variation (OR 1.41). while CT genotype was (30.0%) and (33.03%) in patent and control respectively  with not significantly with OR (14.414) , CC genotype was (46.7%) in patients and (36.70%) in control. The allelic frequency was T patient vs. controls; 38% vs. 47% while allelic frequency was C in the patient vs. controls; 62% vs. 53%. we have concluded that  the MTHFR 677T allele hasn’t  been contributed as a risk factor for myocardial infarction .Our findings raise the possibility that novel genetic defects and/or environmental  factors  may  influence  homocysteine  metabolism  in  this  ethnic  group.Keywords: MetheletetraHydrofolatredctase, Acute myocardial infarction, RFLP-PCR.